Recovery of gastric function in patients affected by chronic atrophic gastritis using l-cysteine (Acetium®): one year survey in comparison with a control group.: L-cysteine and Chronic Atrophic Gastritis - Crafa, Pellegrino; Di Mario, Francesco; Grillo, Simone; Landi, Stefano; Franceschi, Marilisa; Rodriguez-Castro, Kryssia; Tursi, Antonio; Brandimarte, Giovanni; Franzoni, Lorella (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Chronic Atrophic Gastritis (CAG) is a precancerous condition for gastric cancer (GC) as single risk factor, being a consequence of a previous Helicobacter pylori (Hp) infection or based on autoimmune mechanisms. Achlorhydria plays an important role towards the formation of a class I carcinogen, acetaldehyde, after food intake. L-cysteine has been claimed to be able to bind in a covalent way acetaldehyde when administered at means.Methods: In this study we enrolled two CAG groups of patients, one treated whit 300 mg/daily of L-cysteine for one year, the other one untreated.We assessed gastric function lasting the one year follow-up by using non invasive surrogates, i.e. Pepsinogen I (PGI) and gastrin 17 (G17).Results: In the group of 77 CAG on therapy we found a statistically significative increase in PGI values and a decrease in G17 levels, in comparison with unchanged values in control group.Conclusions: L-cysteine seems able to provide a recovery in gastric function when administered in CAG patients and could be proposed as a possible therapy in such patients.